(untitled) (Baghdad Science Journal, 2017)
Gas Lasers are important tools that are used in variety purposes, for their low and (cw) output power. The aim of this study was to prepare a way to calculate an optimum stimulated emission cross-section in a gas laser containing a mixture of Xenon and Neon by (30%-70%). The process was a theoretical study of each gas in separate in terms of their physical properties as an active medium. The results of these calculations are logic and more convenient than other mixtures used before